2021
DOI: 10.18805/lr-4731
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Cluster Bean [Cyamopsis tetragonoloba (L.) Taub] Entrepreneurs in Karnataka

Abstract: Background: Karnataka is predominantly known for cluster bean production. The evidences claims that the cluster bean production is not a profitable option and has many constraints, which hinders farmers to take up this enterprise. The current study aims to analyze the growth in area, to forecast seed demand and to work out the economics of cluster bean production in Karnataka. Methods: The current study was based on the field survey conducted in Karnataka during 2019-20, to collect the primary data from cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Nurseries can be better managed with quality shade net house, poly house, land to keep the plants at growing stage, for display and selling purpose. The capital investment on nursery was found to be economically viable in terms of net present worth, benefit-cost ratio and Internal Rate of Return (Ashoka et al, 2020). Piggery (Rs.…”
Section: Resultsmentioning
confidence: 99%
“…Nurseries can be better managed with quality shade net house, poly house, land to keep the plants at growing stage, for display and selling purpose. The capital investment on nursery was found to be economically viable in terms of net present worth, benefit-cost ratio and Internal Rate of Return (Ashoka et al, 2020). Piggery (Rs.…”
Section: Resultsmentioning
confidence: 99%
“…These results are similar to the finding of Jitender et al [21], in a study of 25 genotypes, guar gum content was found to be in the range of 22.44% to 29.50%. Similarly, Reddy et al [11], in the study consisting of 51 genotypes recorded gum content to be in the range of 16.86 % to 33.10% [22][23][24][25].…”
Section: Seed Yield Per Plantmentioning
confidence: 93%
“…Ashoka et al [22] conducted his study in Karnataka on cluster bean to work out the economics of cluster bean production. The total cost of cultivation per acre was calculated to be ₹ 35,176.…”
Section: Singh Et Al (2018) Conducted His Study In Hisarmentioning
confidence: 99%
“…From the analysis of the data, it was found that the most important restraints faced by the farmers in the production of isabgol production are insect and disease damage to crops. Ashoka et al [22] researched on cluster beans in Karnataka and concluded that the production of cluster beans is subject to a number of limitations and is not a financially viable alternative for producers, which discourages farmers from choosing this crop. The main obstacles found in the cluster bean sector were the high wage rate and the unavailability of high yielding varieties or hybrid seeds.…”
Section: Singh Et Al (2018) Conducted His Study In Hisarmentioning
confidence: 99%